What Does Economic Evaluation Mean in the Context of Children at the End of Their Life? - Sebastian Hinde (MDPI AG, 2021)
The ‘conventional framework’ of economic evaluation, the comparative public sector healthcare costs and quality adjusted life year (QALY) of two or more interventions, has become synonymous with commissioning decisions in many countries. However, while useful as a framework in guiding value-based decisions, it has limited relevance in areas such as end of life care in children and young people, where the costs fall across multiple stakeholders and QALY gains are not the primary outcome. This paper makes the case that the restricted relevance of the ‘conventional framework’ has contributed to the inconsistent and varied provision of care in this setting, and to the knock-on detrimental impact on children nearing the end of their lives as well as their families. We explore the challenges faced by those seeking to conduct economic evaluations in this setting alongside some potential solutions. We conclude that there is no magic bullet approach that will amalgamate the ‘conventional framework’ with the requirements of a meaningful economic evaluation in this setting. However, this does not imply a lack of need for the summation of the costs and outcomes of care able to inform decision makers, and that methods such as impact inventory analysis may facilitate increased flexibility in economic evaluations.